Long‐term course of Crohn's disease in Japan: Incidence of complications, cumulative rate of initial surgery, and risk factors at diagnosis for initial surgery. Issue 12 (December 2015) - Sato, Yuho; Matsui, Toshiyuki; Yano, Yutaka; Tsurumi, Kozue; Okado, Yuki; Matsushima, Yu; Koga, Akihiro; Takahashi, Haruhiko; Ninomiya, Kazeo; Ono, Yoichiro; Takatsu, Noritaka; Beppu, Takahiro; et al.
Abstract: Background and Aims: Intestinal complications of stenosis or fistula may occur during the course of Crohn's disease (CD), and surgery is performed in a fair number of patients. The risk factors for initial surgery in a Japanese hospital‐based cohort of CD patients were evaluated. Methods: This study was a single‐center, retrospective, cohort study. The subjects were 520 patients who underwent inpatient and outpatient treatment at our hospital, had a definitive diagnosis of CD, and no previous surgery. Three parameters were investigated: (i) cumulative incidence of stenosis and fistula; (ii) cumulative rate of initial surgery for each disease type; and (iii) risk factors at diagnosis for initial surgery. Results: (i) Stenosis and fistula increased with time, with stenosis or fistula appearing in about half of the patients after 5 years. (ii) The cumulative rate of initial surgery was about 50% after 10 years. (iii) The patient factors at diagnosis of current smoker, upper gastrointestinal disease, stricturing, penetrating, moderate to severe stenosis of the jejunum, moderate to severe stenosis of the ileum, and moderate to severe stenosis of the terminal ileum were risk factors for initial surgery. Conclusions: Stenosis or fistula appeared in about half of the patients after 5 years from diagnosis. When upper gastrointestinal disease or complicated small intestinal lesions are seen at the time of diagnosis, the cumulative rate of initial surgery is significantly higher.